Full Dollarization : The Pros and Cons - Borensztein, Eduardo (Economic Issues; Economic Issues ;, 2000)
Analyzes the costs and benefits of full dollarization, or the adoption by one country of another country's currency. Potential advantages include lower borrowing costs and deeper integration into world markets. But countries lose the ability to devalue, and become dependent on the U.S. Compares with currency board option.